2016
DOI: 10.1074/jbc.m115.688374
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum-resident Heat Shock Protein 90 (HSP90) Isoform Glucose-regulated Protein 94 (GRP94) Regulates Cell Polarity and Cancer Cell Migration by Affecting Intracellular Transport

Abstract: Heat shock protein 90 (HSP90) is a molecular chaperone that is up-regulated in cancer and is required for the folding of numerous signaling proteins. Consequently, HSP90 represents an ideal target for the development of new anti-cancer agents. The human HSP90 isoform, glucose-regulated protein 94 (GRP94), resides in the endoplasmic reticulum and regulates secretory pathways, integrins, and Toll-like receptors, which contribute to regulating immunity and metastasis. However, the cellular function of GRP94 remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Notably, we demonstrate that these events also occur during cell migration and assembly of uropod-like WRAMP structures, suggesting a common mechanism to regulate PM retraction and cytoskeletal dynamics during PFT-induced PM blebbing and cell migration [21,22,29]. Consistent with our findings, NMII has established roles in both processes [28,33] and Gp96 was recently shown to promote cell polarity and migration [34,35]. How the NMHCIIA-Gp96 interplay coordinates cytoskeleton dynamics and PM remodelling remains elusive.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Notably, we demonstrate that these events also occur during cell migration and assembly of uropod-like WRAMP structures, suggesting a common mechanism to regulate PM retraction and cytoskeletal dynamics during PFT-induced PM blebbing and cell migration [21,22,29]. Consistent with our findings, NMII has established roles in both processes [28,33] and Gp96 was recently shown to promote cell polarity and migration [34,35]. How the NMHCIIA-Gp96 interplay coordinates cytoskeleton dynamics and PM remodelling remains elusive.…”
Section: Discussionsupporting
confidence: 89%
“…Different studies have suggested that polarized secretion of lysosomes and redistribution of ER and/or endosomal compartments regulate uropod dynamics and trailing edge retraction during migration of cancer cells or leucocytes [22,36]. We show that ER and LAMP1-positive compartments localized within NMHCIIA bundles and Gp96 was proposed to modulate polarity via vesicular trafficking [35]. Additionally, NMHCIIA can control polarized secretion [37] and organelle positioning [38] and was recently shown to mediate lysosomal exocytosis in PFT-wounded cells [39].…”
Section: Discussionmentioning
confidence: 65%
“…The main function of this protein is in the folding of other proteins. However, other members of heat shock protein family have been shown to be upregulated in cancer and play a role in immune system and metastasis . The levels of glucose‐regulated protein 94, which is an isoform of heat shock protein 90 were compared in two replicates of cancer tissues of prostate, BC metastatic to liver, and lung cancer versus normal tissues from the same person using Western blot analysis and no heat shock protein 90 was observed in controls, but there were positive results for cancer samples .…”
Section: Resultsmentioning
confidence: 99%
“…42 Similarly, selective inhibition of Grp94 resulted in the degradation of integrin α 2 (Figure 7A,B). Integrin α 2 forms a heterodimer with integrin β 1 on the cell surface, 38 which is responsible for binding to collagen in the extracellular matrix to promote metastasis and invasion.…”
Section: Grp94-selective Inhibition In Cancermentioning
confidence: 86%